Ultrafast pump-probe platform for broadband and polarization-resolved characterization of materials: case study of octupolar push-pull azobenzenes - Garcia, Rafael de Queiroz (2023)
Ultrafast pump-probe techniques have become essential characterization tools for the development of new materials because they are able to obtain information about the dynamic processes that occur in matter when it interacts with light. In this particular kind of spectroscopy, the important processes concern the fs, ps and ns timescales, which are achieved experimentally by employing ultrashort-pulsed lasers in the pump-probe setups. The objective of this work was to build a new pump-probe platform in the laboratory with time resolution between 150 and 250 fs, tunable pump and probe sources from the UV to the MIR range (210 - 3000 nm), and with lock-in based signal acquisition for increased signal-to-noise ratio. In addition, a spectrometer-based setup was also developed for acquisition with a broadband probe. This setup was mainly used in the form of a transient absorption and transient absorption anisotropy experiment. However, it can be easily adaptable for different pump-probe experiments and also several kinds of samples. To test the setup, measurements on a monolayer MoS2 thin film were performed. The results obtained were in agreement with the literature and have shown the setup is able to measure samples with low absorbance (<0.1). Afterward, a class of four push-pull azobenzenes with octupolar moieties were studied. It was possible to identify two photoisomerization mechanisms happening on the few-ps range and which led to different pathways with also different signatures on the ground state decay. By comparing the four molecules, the effect of inertia, charge symmetry and push-pull strength on the isomerization dynamics was characterized, leading to a comprehensive study of not only the trans but also the cis isomer. Finally, an heterogeneous mixture of perylene aggregates and monomers was studied under two solvent conditions and with variations of the solution temperature. It was possible to characterize the excited state lifetime, the charge transfer signatures of the excited state and also the orientation of transition dipole moments in the aggregate form. With the study of these three samples, the versatility and capabilities of the setup are demonstrated. Additionally, with the implementation of a Noncollinear Optical Parametric Amplifier during the project, with pulses up to 18 fs, the setup will also be able to measure much faster dynamics in the future.